HMGB1 correlates with angiogenesis and poor prognosis of perihilar cholangiocarcinoma via elevating VEGFR2 of vessel endothelium - Xu, Yun-Fei; Liu, Zeng-Li; Pan, Chang; Yang, Xiao-Qing; Ning, Shang-Lei; Liu, Hong-Da; Guo, Sen; Yu, Jin-Ming; Zhang, Zong-Li (Oncogene, 2019)
Perihilar cholangiocarcinoma (PHCCA) is the most common type of cholangiocarcinoma with low resection rate and high morbidity. The study of PHCCA biomarkers made progresses slowly compared with intrahepatic cholangiocarcinoma because of surgical complexity and low possibility of radical surgery, which resulted in the difficulty of specimen obtainment. To screen and identify new biomarkers in PHCCA, we constructed a retrospective cohort with 121 PHCCA patients and a prospective cohort consisting of 64 PHCCA patients, and screened the candidate biomarkers by immunohistochemistry and quantified PCR. In our study, expression of high mobility group box 1 (HMGB1) was demonstrated to be significantly associated with microvascular density (MVD) and unfavorable prognosis of PHCCA in both retrospective and prospective study. Moreover, HMGB1 concentrations in bile and serum of PHCCA patients and healthy controls were detected and compared. Postoperative serum HMGB1 and reflux cholangitis indicated recurrence and unfavorable prognosis of PHCCA. With experiments in vitro and in vivo, we demonstrated that intracellular HMGB1 could be released from PHCCA cells and induce invasion and angiogenesis with LPS stimulation. VEGFR2 expression in vessel endothelial cells was upregulated by the released HMGB1 from PHCCA, resulting in the ectopic angiogenesis. In conclusion, intracellular HMGB1 could be released from PHCCA cells and promote angiogenesis via elevating VEGFR2 in vessel endothelial cells. High expression of HMGB1 was associated with MVD and poor prognosis in clinical analyzation. Postoperative serum HMGB1 and cholangitis could predict high recurrence and unfavorable prognosis.